Synthesis and investigation of coordinative properties of biimidazole-derived ligands - Bulatova, Margarita (2015)
For this thesis a study of the coordination properties of biimidazole-based compounds was performed. The thesis is divided into two parts: literature part, where the chemistry and application of biimidazole and its derivatives are discussed, and experimental part, where the synthesis and coordination properties of biimidazole-based ligands are studied and discussed. The literature part contains a discussion of coordinative properties of biimidazole-derived ligands and a discussion of different types of weak interactions. Definition, nature and examples of hydrogen and different types of π-bonding were considered in detail. Due to chemical properties of biimidazole-derived compounds they have been applied in medicine, supramolecular chemistry, and coordination chemistry. A short overview of these applications presented in the literature part. The experimental part contains synthetic procedures of several biimidazole-based ligands with promising supramolecular properties. The ability of the synthesized ligands to bind d-block transition metals such as Fe(II), Zn(II), Ru(II), Ag(I), Re(III), Pt(II), Au(I) was studied. A variety of coordination frameworks were synthesized using biimidazole-based compounds. In addition, a novel coordination compound of biimidazole-based ligand and potassium iodide was synthesized and investigated.